Dogancay : Blue Walls of New York. - Antmen, Ahu (Istanbul : Türkiye Is Bankasi A.S. Istanbul, 2003)
Traveling from city to city in pursuit of the walls of the world since the seventies, Dogancay has recently focused his attention on the Blue Walls of New York... Immortalizing the energy reflected from these temporary walls during the refurbishment of the N.Y. subway, this is another series that becomes visual testimony to life in the big city : Blue Walls of New York.
Chronology p. 117-119
ind. tent., gr. tent., coll. p. 120-123
Engels
boek
Keywords: Dogançay, Burhan; New York